Factors Affecting Career Satisfaction among Dentists of Pakistan - hmad Liaquat, Ehsanul Haq, Aiman Gull, Ayesha Sadiqa, Muhammad Abbas, Muhammad Rashid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: career satisfaction is considered as the amount or degree of gratification and contentment that a dentist fosters towards his/her overall job, factoring into that equation his/her satisfaction with the job itself, the peers at the job, the supervisors, and the policies at work. Aim: To identify the factors that hinder dentists’ jobs and their satisfaction levels. Methods: The study was conducted over the period of two and half months at Lahore University College of Medicine and Dentistry. Sample size 194 was calculated and data were analyzed with simple descriptive statistics. This study was approved ethically by the ethical review committee of the University College of Dentistry, University of Lahore. Results: Results showed there were some areas of dentistry that requires new policies for improvement. Conclusion: Time to incorporate new technologies, learning new skills, and career aspirations show a high level of satisfaction while leisure time, income and opportunities for quality care are the least satisfying areas. Keywords: career, satisfaction, dentistry,